Knowledge of Transmission Patterns of HIV/AIDS and the place of Health Counselling among Students of Tertiary Institutions in Kwara State, Nigeria - Oniye, Abdulrazaq; Olaitan, Olukunmi Lanre; Olawuyi, Bolanle (NIU Journal of Social Sciences; Vol 3 No 2 (2017): KIU Journal of Social Sciences, Vol. 3 No. 2, September 2017, 2017)
This study investigated knowledge of transmission patterns of HIV/AIDS and the place of counselling among students of tertiary institutions in Kwara State, Nigeria. A proportionate sampling technique was used to select 700 students from five tertiary institutions in Kwara State. The hypotheses formulated were tested using Chi-square and analysis of variance (ANOVA) at Âµ = 0.05 level of significance. In the findings, calculated X 2 value of 124.69 revealed that the students have adequate knowledge about HIV/AIDS transmission through sexual contacts, also calculated x 2 value of 67.83 revealed that students have adequate knowledge that HIV/AIDS can transmit through mother to child and the ANOVA result of 3.52 showed that students of various tertiary institutions in Kwara State have varied knowledge about HIV/AIDS transmission in health care setting. Fisher least significance difference was used as multiple range comparison test to identity where the significant difference between and within the group of students. Health counselling is not fully in place to influence studentsâ€™ knowledge. Based on the findings, it was recommended that AIDS education to include STDs, sexuality and reproductive health education should be made compulsory and be incorporated into the syllabi and curricula from primary, secondary and tertiary institutions. Also, Health Counselling unit should be established in our institutions in Nigeria in Nigeria. Keywords: Knowledge, Transmission patterns, HIV/AIDS, Health counselling, Tertiary institutions